Internal arteriovenous fistula extravascular stent and preparation method thereof
By synthesizing low molecular weight PLCL diol and performing double bond modification, bioabsorbable elastomer resin suitable for ultraviolet curing 3D printing was prepared, and extravascular stents were designed and prepared to improve the maturity of arteriovenous fistulas, which solved the problem of The lack of mechanical properties of existing photopolymeric materials has achieved high-precision printing and drug loading, and improved the maturity and hemodynamics of arteriovenous fistulas.
Patent Information
- Application Number
- CN202411556634.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
AI Technical Summary
The lack of mechanical properties of existing photopolymeric materials, especially the lack of photocurable elastomer resin that can match elastic tissues such as human cartilage, blood vessels and skin, leads to the problem of maturity failure in the extravascular stent of arteriovenous fistula.
By synthesizing low molecular weight, low viscosity PLCL diol and performing double bond modification, bioabsorbable elastomer resin suitable for ultraviolet curing 3D printing was prepared, and extravascular vascular to improve the maturity of arteriovenous fistula is designed and prepared. Bracket. The stent adopts a "y" structure, combining bioabsorbable elastomer resin and a hydrogel layer, providing mechanical support and drug sustained release.
Achieve high-precision printing and drug loading, provide mechanical properties similar to human blood vessels, improve the maturity of arteriovenous fistula, reduce neointimal hyperplasia and thrombosis, and improve the formation of sustained drug release and mechanical support. hemodynamics.
Smart Images

Figure BDA0005116646230000071 
Figure BDA0005116646230000081 
Figure BDA0005116646230000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new biomedical materials, and specifically discloses an arteriovenous fistula extravascular stent and a preparation method of the stent. Background Art
[0002] Globally, approximately 5.7 million people suffer from end-stage renal disease, and hemodialysis remains the most common method of replacing kidney function. In hemodialysis, arteriovenous fistula (AVF) is widely considered the gold standard for vascular access because it has a lower risk of infection and requires fewer maintenance interventions than other methods. However, data show that up to 60% of patients using AVFs fail to successfully mature for hemodialysis. The main reasons for AVF maturation failure include inflammatory response, suboptimal anastomotic angles, and changes in hemodynamics, which together lead to neointimal hyperplasia (NIH) and thrombosis.
[0003] Specifically, changes in hemodynamics can cause areas of low wall shear stress (TAWSS), high oscillatory shear index (OSI), and high wall shear stress fluctuation (RRT) in the vascular wall, which promote neointimal hyperplasia. At the same time, in response to vascular injury, activated inflammatory cells, platelets, and vascular smooth muscle cells (VSMCs) release growth factors, especially platelet-derived growth factor (PDGF), which causes VSMCs to transform from a quiescent contractile phenotype to a dedifferentiated synthetic phenotype. In addition, reactive oxygen species (ROS) further promote the phenotypic conversion of VSMCs in response to vascular injury by activating the NF-kB signaling pathway. The combined effect of the above factors leads to the migration of VSMCs to the intima, causing NIH. Although balloon angioplasty and stenting can be used as remedial measures, these interventions often increase treatment costs and patient morbidity, thereby reducing the cumulative survival rate of AVF. Therefore, there is an urgent need to develop effective strategies to prevent AVF maturation failure.
[0004] Over the past few decades, additive manufacturing (AM) technology has rapidly developed into a powerful tool for manufacturing implantable objects based on biomaterials. This technology is capable of creating implants with complex geometric structures that can help tissue regeneration. Photolithography, especially stereolithography (SLA) and digital light processing (DLP), with its excellent spatial resolution, can accurately simulate the complex structure of human tissue, thereby providing highly customized solutions for patients. However, the application of photocurable biomaterials is still limited, mainly due to the shortcomings of existing photopolymerizable materials in mechanical properties. Current photopolymerizable biomaterials mainly include softer gel formulations (0.1-100kPa) and harder highly cross-linked resins (100MPa), but their ultimate breaking strength is usually less than 100%. This shows that there is a lack of photocurable elastomeric resins (low MPa, high elongation) on the market that can match elastic tissues such as human cartilage, blood vessels and skin.
[0005] Poly(L-lactide-co-ε-caprolactone) (PLCL) is a material copolymerized by L-lactic acid (LLA) and caprolactone (CL). PLCL not only has the advantages of monomers, such as good biocompatibility, non-toxic degradation products, biodegradability and drug permeability, but also makes up for the slow degradation of poly(ε-caprolactone) (PCL). PLCL behaves similarly to non-absorbable polyurethane materials and silicone materials in terms of strength and toughness, belongs to the range of elastomers, and its mechanical properties are similar to those of human soft tissue. PLCL has been shown to have excellent tissue compatibility, biodegradability and plasticity, and is therefore widely used in the field of bioscaffold materials. However, ordinary high molecular weight PLCL has a high processing viscosity and can only be processed by melt extrusion FDM 3D printing technology, which results in low printing accuracy and a printing temperature as high as 170°C, which makes in situ loading of drugs difficult.
[0006] Therefore, there is an urgent need for a PLCL resin material with high mechanical properties and low printing temperature to meet the needs of high-precision printing and drug loading. Summary of the invention
[0007] In view of the problems and shortcomings in the prior art, the present invention aims to provide a bioabsorbable elastomeric resin suitable for UV-curing 3D printing, and based on this resin, design and prepare an extravascular stent for improving the maturity of arteriovenous fistula (AVF).
[0008] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:
[0009] An arteriovenous fistula extravascular stent, the extravascular stent is prepared by 3D printing using a bioabsorbable elastomeric resin as printing ink, the extravascular stent comprises a tubular arterial stent and a tubular venous stent, the venous stent is anastomosed to the tube wall of the arterial stent at an angle of 30 to 60 degrees to form a "y"-shaped structure; a first notch is provided on the tube wall of the arterial stent, opposite to the anastomosis between the arterial stent and the venous stent, the first notch extending from one end of the tubular arterial stent to the other end; a second notch is provided at the inner side of the angle between the venous stent and the arterial stent anastomosis, extending downward from the two tube openings at the top of the "y"-shaped structure to the anastomosis.
[0010] The bioabsorbable elastomer resin is prepared by the following steps:
[0011] Step S1: preparing PLCL diol;
[0012] Step S2: subjecting the terminal hydroxyl groups in the PLCL diol to an acyl chloride, anhydride or glycidyl ester with a carbon-carbon double bond to esterification or transesterification reaction, thereby double-bond-modifying the PLCL diol to obtain A-PLCL;
[0013] Step S3: A-PLCL is mixed with a cross-linking agent, a free radical inhibitor, and a photoinitiator to obtain a bioabsorbable elastomeric resin that can be used as 3D printing ink.
[0014] The specific method for preparing PLCL diol in step S1 is: adding lactide, ε-caprolactone, diol, and stannous octoate into a reaction kettle, stirring and reacting at 130-160° C. under vacuum and anaerobic conditions for 8-16 hours to obtain poly (L-lactide-co-ε-caprolactone) diol, that is, PLCL diol.
[0015] Preferably, the molecular weight of PLCL diol is 3000-10000, and the viscosity is less than 1000 Pa·s; in step S1, the molar ratio of lactide, ε-caprolactone and diol is 1:1:(0.033-0.088); the diol is selected from one or more of 1,6-hexanediol, ethylene glycol or triethylene glycol.
[0016] In step S2, the acid chloride, acid anhydride and glycidyl ester with a carbon-carbon double bond as the modifier are methacryloyl chloride, methacrylic glycidyl ester and methacrylic anhydride respectively.
[0017] Step S2 specifically comprises dissolving PLCL in a dichloromethane solution, then adding a modifier and triethylamine, and reacting at room temperature for 20 to 24 hours;
[0018] The molar ratio of the modifier, triethylamine and PLCL diol is 4:4:1; and the concentration of dichloromethane is 15% to 40%.
[0019] In step S2, PLCL diol is dissolved in a dichloromethane solution to reduce viscosity and facilitate stirring during the reaction; triethylamine is used as an acid binding agent to neutralize HCl generated during the reaction of the modifier.
[0020] Preferably, in step S3, based on the weight of A-PLCL as a quantitative basis, 1% to 20% of a crosslinking agent, 0.05% to 2% of a free radical inhibitor, and 0.2% to 3% of a photoinitiator are added;
[0021] The crosslinking agent is pentaerythritol tetrakis-3-mercaptopropionate, the free radical inhibitor is 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical (Tempol) or 2,2,6,6-tetramethylpiperidin oxide (Tempo), and the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) or 2,4,6-trimethylbenzoyl ethylphosphonate (TPO-L).
[0022] Among them, the addition of -SH can react with acrylate to form ene-thiol reaction, R-SH+CH2=CHR'→RS-CH2CH2R', where R-SH represents thiol, CH2=CHR' represents olefin, and the sulfhydryl group (SH) in thiol adds to the carbon-carbon double bond in olefin to form a thioether bond (SC) and a new carbon-carbon single bond. The reaction rate is faster than the reaction of the carbon-carbon double bond, so -SH will react before the acrylate itself, thereby improving the cross-linked network topology.
[0023] The inner surface of the extravascular stent body is also coated with hydrogel; the hydrogel is one of methacrylated silk fibroin, methacrylated gelatin, methacrylated hyaluronic acid, methacrylated chitosan, methacrylated sodium alginate, methacrylated chondroitin sulfate or polyethylene glycol acrylate.
[0024] The extravascular stent body and the hydrogel layer are both loaded with drugs. The drugs loaded in the extravascular stent body are selected from one or more of rapamycin, paclitaxel, and 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical; the drug loaded in the gel layer is 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical.
[0025] The method for preparing an arteriovenous fistula external stent comprises the following steps:
[0026] (1) Measure the size of the blood vessels based on the patient's ultrasound, CT or MRI results, and use SolidWorks software to build an extravascular stent model that matches the patient's blood vessel size;
[0027] (2) Mix the drug into the 3D printing ink, import it into the built stent model, set the heating temperature to 50°C, and perform 3D printing;
[0028] (3) After printing is completed, the stent is placed in anhydrous ethanol for ultrasonic treatment for 10 to 15 minutes, and then cured under a 365 to 405 nm ultraviolet lamp for 10 to 15 minutes to obtain the extravascular stent body.
[0029] Preferably, after the arteriovenous fistula is formed, the extravascular stent body is put outside the arteriovenous fistula, the hydrogel is injected into the gap between the extravascular stent body and the blood vessel using a syringe, and a 365-405nm ultraviolet lamp is used to irradiate and cure for 10-12 minutes to obtain a double-layer arteriovenous fistula extravascular stent.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The present invention synthesizes low molecular weight, low viscosity PLCL diol and performs double bond modification on it, and the obtained A-PLCL successfully solves the problems of low 3D printing accuracy and difficulty in drug loading caused by high viscosity while retaining the advantages of PLCL. The obtained photocurable material has low modulus and high elongation at break, which effectively solves the problem that the mechanical properties of biodegradable printing materials in the existing photocurable material library are too strong and difficult to match with human tissue, filling the technical gap of photocurable biodegradable elastomer resin materials.
[0032] (2) The A-PLCL stent layer in the present invention has a low elastic modulus and a high elongation at break, and its mechanical properties are similar to those of human blood vessels. It can provide mechanical support for the anastomosis and fix the anastomotic shape of the arteriovenous fistula at the optimal angle. The "y"-shaped structure with a single-sided opening reduces the difficulty of stent installation and eliminates the need for sutures. The "y"-shaped single-sided opening design combined with the low modulus and high deformation characteristics of the A-PLCL elastomer can perfectly fit the blood vessels while providing sufficient support and not hindering the outward remodeling of the blood vessels. After the stent is installed, the "funnel effect" of the stent increases the blood flow velocity, improves the hemodynamics at the anastomosis, reduces stress concentration, and guides vascular remodeling.
[0033] (3) The A-PLCL layer in the present invention has a sustained release property after loading the drug, while the methacrylylated silk fibroin (SilMA) hydrogel layer has a burst release property of the drug. By combining drugs with different properties, the advantages of the extravascular stent in local drug administration can be further exerted. The present invention solves the problem of venous smooth muscle proliferation and migration caused by hemodynamic changes and inflammation in patients with arteriovenous fistula after surgery through the mechanical support of the extravascular stent and the sustained release of local drugs, and reduces the formation of neointimal hyperplasia (NIH) and thrombus.
[0034] (4) Tempol of the present invention, as a free radical inhibitor, not only has the effect of scavenging ROS, but also can improve the accuracy of 3D printing. When used in combination with rapamycin, it can enhance the inhibitory effect on smooth muscle cells, thereby inhibiting intimal hyperplasia (NIH), thereby improving the maturity of arteriovenous fistula. At the same time, it effectively induces the contractile phenotype of VSMC and produces significant changes in cell morphology and function, further supporting their synergistic effect in inhibiting intimal hyperplasia and promoting vascular maturation. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The 3D renderings and finished product images of the arteriovenous fistula extravascular stent of the present invention are shown;
[0036] Figure 2 This is a schematic diagram of the preparation and application process of the light-cured biodegradable elastomer 3D printed scaffold of the present invention;
[0037] Figure 3 Schematic diagram of the preparation and cross-linking mechanism of the photocurable biodegradable elastic resin of the present invention;
[0038] Figure 4 This is a flow chart of 3D printing of an extravascular stent in Example 1;
[0039] Figure 5 This is a comparison chart of the nuclear magnetic resonance results of the photosensitive resin in Example 1 before and after modification;
[0040] Figure 6 The mechanical properties test diagram of Example 1-4A-PLCL / 4SH;
[0041] Figure 7 It is the degradation test diagram of Example 1-4A-PLCL / 4SH;
[0042] Figure 8 It is the viscosity test graph of Example 1~4A-PLCL / 4SH;
[0043] Fig. 9 The water contact angle test diagram of Examples 1 to 4A-PLCL / 4SH;
[0044] Fig.10 The in vitro biocompatibility test results of Examples 1 to 4A-PLCL / 4SH are shown;
[0045] Fig.11 The in vivo biocompatibility test results of Examples 1 to 4A-PLCL / 4SH are shown;
[0046] Fig.12 This is the fluid-structure coupling simulation result diagram before and after the external stent is implanted;
[0047] Fig.13 The mechanical properties test diagram of Examples 5 to 6A-PLCL / 4SH;
[0048] Fig.14 The figure shows the inhibitory effect of dual administration of Tempol and rapamycin (RAPA) on smooth muscle cell proliferation;
[0049] Fig.15 This is a diagram showing the ROS removal effect of the extravascular stent;
[0050] Fig.16 This is a diagram showing the smooth muscle cell inhibition effect of an extravascular stent;
[0051] Fig.17 It is the drug release diagram of Tempol and rapamycin (RAPA);
[0052] Fig.18 This is a photo of the application test of extravascular stents in rats;
[0053] Fig.19 This is the HE staining result of the venous section near the anastomosis of the rat. DETAILED DESCRIPTION
[0054] It should be noted that the following detailed description is exemplary and is intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein shall have the same meaning as those generally understood by those of ordinary skill in the art to which the present invention belongs. For the experimental methods in the following examples where specific conditions are not specified, conventional techniques in the art or conditions recommended by the manufacturer are used; if the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased on the market.
[0055] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the present invention is now further described in detail through specific embodiments, but these embodiments should not be regarded as limiting the scope of the present invention.
[0056] (I) Effect of different molecular weights on material properties
[0057] Example 1
[0058] An arteriovenous fistula extravascular stent, the extravascular stent is prepared by 3D printing using a bioabsorbable elastomer resin as printing ink, the 3D rendering and finished product of the extravascular stent are as follows Figure 1 As shown by Figure 1It can be seen that the extravascular stent includes a tubular arterial stent and a tubular venous stent, and the venous stent is anastomosed with the wall of the arterial stent at an angle of 60° to form a "y"-shaped structure; a first notch is provided on the wall of the arterial stent, opposite to the anastomosis of the arterial stent and the venous stent, and the first notch extends from one end of the tubular arterial stent to the other end; a second notch is provided on the inner side of the angle between the anastomosis of the venous stent and the arterial stent, extending downward from the two tube openings at the top of the "y"-shaped structure to the anastomosis. The specific size of the stent can be adjusted according to the outer diameter of the patient's blood vessel, and the inner diameter of the stent should match the outer diameter of the patient's blood vessel after expansion (generally 150%-200% of the outer diameter before surgery).
[0059] The preparation process of the arteriovenous fistula extravascular stent is as follows: Figure 2 As shown, the preparation steps include:
[0060] Step S1: Synthesis of PLCL-3000
[0061] First, a Schlenk reaction bottle equipped with a magnetic stirrer was flame dried. Then, 25.99 g (0.227 mol) of ε-caprolactone, 32.82 g (0.227 mol) of lactide, 2.36 g (0.02 mol) of 1,6-hexanediol and 0.3 g (0.741 mmol) of Sn (Oct) 2 were added to the bottle, wherein the molar ratio of lactide, ε-caprolactone and 1,6-hexanediol was 1:1:0.088. After that, nitrogen was purged for 30 minutes, and a vacuum machine was used to draw a vacuum for 30 minutes to form a vacuum oxygen-free state. Then, the reactants were stirred at 150 ° C for 16 hours to obtain the final product PLCL-3000.
[0062] Step S2: Olefin functionalization of PLCL (A-PLCL synthesis)
[0063] PLCL diol was dissolved in a 15% dichloromethane solution, and then methacryloyl chloride (0.908 mol) and triethylamine (0.908 mol) were added and reacted at room temperature for 24 h. The final product A-3000 was obtained by precipitation in cold anhydrous ethanol. Step S3: Mixing of A-3000 / 4SH
[0064] Based on the weight of 6 g (0.002 mol) of A-3000 as a quantitative basis, 8.15% pentaerythritol tetrakis-3-mercaptopropionate, 0.1% Tempol and 1% TPO-L were added, and magnetic stirring was performed for 2 h until the mixture was uniformly mixed to obtain A-3000 / 4SH.
[0065] A-PLCL / 4SH was prepared through steps S1 to S3. Its preparation and cross-linking mechanism are as follows: Figure 3 shown.
[0066] Step S4: Preparation of an arteriovenous fistula extravascular stent, comprising the following steps:
[0067] (1) Measure the size of the blood vessels based on the patient's ultrasound, CT or MRI results, and use SolidWorks software to build an extravascular stent model that matches the patient's blood vessel size;
[0068] (2) Import the 3D printing ink into the built bracket model, set the heating temperature to 50°C, and perform 3D printing. The printing process is as follows Figure 4 As shown;
[0069] (3) After printing is completed, the stent is placed in anhydrous ethanol for ultrasonic treatment for 10 minutes, and then cured under a 365-405 nm ultraviolet lamp for 10 minutes to obtain the extravascular stent body.
[0070] Example 2
[0071] Only steps S1, S2 and S3 in Example 1 were completed, and the other steps were basically the same as those in Example 1, except that:
[0072] In step S1, the amount of 1,6-hexanediol added is 4.73 g (0.04 mol), the molar ratio of lactide, ε-caprolactone, and 1,6-hexanediol is 1:1:0.176, and the final product is PLCL with a molecular weight of 1500, PLCL-1500;
[0073] In step S2, the final product is A-1500;
[0074] In step S3, the addition amount of pentaerythritol tetrakis-3-mercaptopropionate is 16.3%, and the final product is A-1500 / 4SH.
[0075] Example 3
[0076] Only steps S1, S2 and S3 in Example 1 were completed, and the other steps were basically the same as those in Example 1, except that:
[0077] In step S1, the amount of 1,6-hexanediol added is 1.18 g (0.01 mol), the molar ratio of lactide, ε-caprolactone, and 1,6-hexanediol is 1:1:0.044, and the final product is PLCL with a molecular weight of 6000, PLCL-6000;
[0078] In step S3, the addition amount of pentaerythritol tetrakis-3-mercaptopropionate is 4.1%, and the final product is A-6000 / 4SH.
[0079] Example 4
[0080] Only steps S1, S2 and S3 in Example 1 were completed, and the other steps were basically the same as those in Example 1, except that:
[0081] In step S1, the amount of 1,6-hexanediol added is 0.89 g (0.0075 mol), the molar ratio of lactide, ε-caprolactone, and 1,6-hexanediol is 1:1:0.033, and the final product is PLCL with a molecular weight of 8000, PLCL-8000;
[0082] In step S3, the addition amount of pentaerythritol tetrakis-3-mercaptopropionate is 3.1%, and the final product is A-8000 / 4SH.
[0083] Table 1 shows the theoretical molecular weight, molecular weight calculated by H NMR spectrum and molecular weight of PLCL under different initiator ratios (molar ratio of caprolactone monomer and lactide monomer to initiator) of Examples 1 to 4. The results show that the molecular weight of PLCL decreases with the addition of initiator and has regularity. This shows that PLCL with different molecular weights can be synthesized by adjusting the initiator ratio.
[0084] Table 1 Polymer properties of Examples 1 to 4
[0085]
[0086] Performance Test:
[0087] (1) Nuclear magnetic resonance hydrogen spectrum test
[0088] A-3000 of Example 1 and A-PLCL after double bond modification were subjected to hydrogen spectrum test. The results are as follows: Figure 5 , Figure 5 The 1H-NMR spectra of A-3000 before and after modification were displayed, and the results showed that new peaks appeared at 5.8 and 6.2 ppm, indicating that the methacrylic acid functional group had been successfully connected to the end of PLCL.
[0089] (2) Mechanical properties test
[0090] The A-PLCL and A-PLCL / 4SH prepared in Examples 1 to 4 were subjected to tensile tests and elastic modulus tests. The results are as follows: Figure 6 And as shown in Table 2.
[0091] Table 2 Mechanical properties of materials in Examples 1 to 4
[0092]
[0093] Depend on Figure 6As can be seen from Table 2, the mechanical properties of the material are improved by introducing -SH. Compared with pure A-PLCL, the elastic modulus of A-PLCL / 4SH is reduced, indicating that the flexibility of the material under stress is enhanced. The ultimate tensile stress of A-PLCL / 4SH increased by about 50%, indicating that the material can withstand greater tension before breaking. More significantly, the elongation at break increased by 80% to 100%, which means that the material can undergo greater deformation before breaking. The elastic modulus of A-PLCL / 4SH is similar to that of human blood vessels (0.5MPa to 2MPa).
[0094] The A-PLCLs of different molecular weights prepared in Examples 1 to 4 will form networks with different structural characteristics after cross-linking, which directly affects the mechanical properties of the material. As the molecular weight of A-PLCL increases, the chain spacing of the cross-linked network increases, ultimately significantly improving the elongation at break and ultimate tensile stress of the samples.
[0095] (3) Degradability test
[0096] In order to evaluate the degradation behavior of A-PLCL / 4SH, NaOH accelerated degradation test and PBS degradation test were performed on A-PLCL / 4SH prepared in Examples 1 to 4. The experimental results are shown in FIG. Figure 7 a, 7b. The experimental results show that A-PLCL / 4SH has good degradability. In particular, as the molecular weight of A-PLCL increases, the degradation time is significantly prolonged, which indicates that the degradation time of the scaffold can be controlled by selecting A-PLCL / 4SH with different molecular weights.
[0097] (4) Viscosity test
[0098] The viscosity of A-PLCL / 4SH prepared in Examples 1 to 4 was tested. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that as the molecular weight increases, the viscosity increases accordingly. Therefore, it is necessary to control the molecular weight within an appropriate range, taking into account both mechanical properties and printing accuracy.
[0099] (5) Biocompatibility test
[0100] 1. Hydrophilicity test
[0101] The contact angle of A-PLCL / 4SH prepared in Examples 1 to 4 was measured. The experimental results are as follows: Fig. 9 shown. Fig. 9The relationship between the hydrophilicity and molecular weight of A-PLCL / 4SH is shown. As the molecular weight of A-PLCL increases, its contact angle gradually decreases and its hydrophilicity gradually increases, approaching the level of high molecular weight PLCL. This property is beneficial to cell growth because moderate hydrophilicity can promote cell attachment and expansion, thereby improving the biocompatibility of the material.
[0102] 2. Transwell cell co-culture
[0103] To verify the biocompatibility of A-PLCL / 4SH, we co-cultured A-PLCL / 4SH with L929 cells using a transwell system and performed live-dead staining and CCK-8 assays at 1, 3, and 7 days. Fig.10 a, b, c). The results showed that there was no significant difference in cell growth between the A-PLCL groups with different molecular weights and the pure PLCL group. This indicates that A-PLCL exhibits good biocompatibility in a cell culture environment and does not significantly affect cell growth and reproduction regardless of changes in its molecular weight.
[0104] 3. Mouse subcutaneous implantation experiment
[0105] A-PLCL samples with different components were implanted subcutaneously in mice for 1 and 4 weeks ( Fig.11 ). Specifically, 6-8 week old Bcl-2 female mice were used, and an incision was made in the abdomen. The 3D-printed 5×2×2mm implant was placed in the pocket of the abdomen, and the incision was sutured. Three mice were operated on in each group, and two implants were implanted on each side. The control group underwent the same operation using high molecular weight PLCL. The behavior and body weight of the mice were observed during the study, and the mice were euthanized and autopsied at 1 week and 4 weeks after implantation. The implants were fixed together with the surrounding tissues for histopathological evaluation. The experimental results showed that when all components were implanted for one week, mild acute inflammation occurred around the implant tissue, and the inflammation subsided at 4 weeks, and no signs of host immune response were found. This further verified the biocompatibility of A-PLCL in vivo, indicating its safety and reliability in biomedical applications.
[0106] (6) Extravascular stent simulation test
[0107] In order to further study the effect of AVF extravascular stent on improving hemodynamics, vascular deformation and concentrated stress at the AVF anastomosis, the multi-physics finite element simulation software COMSOL was used to perform fluid-solid coupling simulation on arteriovenous fistula (AVF) before and after the stent was used ( Fig.12a, b, c, d). By measuring the diameters of arteries and veins, and establishing an arteriovenous fistula model through soildworks, a vascular stent was further added to the anastomosis, and finally an arteriovenous fistula model with and without a stent was created ( Fig.12 b). Simulation results show that 4-6 weeks after surgery, the arteriovenous fistula without stents will experience changes in anastomotic angle, irregular remodeling of the venous wall, and neointimal hyperplasia due to the lack of effective support at the anastomosis under the action of blood flow. However, the anastomotic angle of the arteriovenous fistula with stent support remains unchanged, and the vein degrades with the degradation of the gel layer and the reduction of the concentrated stress caused by the mechanical support, while the regular remodeling ( Fig.12 a). The use of extravascular stents restrains the uneven expansion of blood vessels at the anastomosis, and the resulting "funnel effect" improves the hemodynamics at the arteriovenous fistula, such as increasing the average wall shear stress (TAWSS), reducing the wall shear oscillation index (OSI) and relative stagnation time (RRT) ( Fig.12 c). Among them, areas with high OSI indicate frequent changes in blood flow direction, which can easily cause dysfunction of vascular endothelial cells and increase the risk of atherosclerosis. Low OSI indicates that the blood flow direction is relatively stable, which has a protective effect on blood vessels. Higher TAWSS usually occurs in areas with smooth blood vessel flow, such as straight parts of blood vessels. This situation helps to maintain the normal function of vascular endothelial cells and reduce the risk of atherosclerosis. Areas with high RRT are usually accompanied by low WSS and high OSI. Such areas are prone to blood retention, promoting thrombosis and intimal hyperplasia (such as the occurrence of atherosclerosis). In addition, the extravascular stent provides the necessary mechanical support for the arteriovenous fistula anastomosis, ensures the anastomotic angle, and reduces uneven deformation and concentrated stress at the anastomosis ( Fig.12 d).
[0108] (II) Effect of different pentaerythritol tetrakis-3-mercaptopropionate addition amounts on material properties
[0109] Example 5
[0110] Only steps S1, S2 and S3 in Example 1 were completed, and the other steps were basically the same as those in Example 1, except that:
[0111] In step S3, the addition amount of pentaerythritol tetrakis-3-mercaptopropionate is 2.05%, and the corresponding bioabsorbable elastomer resin is recorded as A-3000 / 4SH-2.
[0112] Example 6
[0113] Only steps S1, S2 and S3 in Example 1 were completed, and the other steps were basically the same as those in Example 1, except that:
[0114] In step S3, the addition amount of pentaerythritol tetrakis-3-mercaptopropionate is 1.4%, and the corresponding bioabsorbable elastomer resin is recorded as A-3000 / 4SH-3.
[0115] The mechanical properties of A-PLCL and A-PLCL / 4SH prepared in Examples 5 to 6 were tested, including tensile test and elastic modulus test. The results are as follows: Fig.13 shown.
[0116] Comparing the A-PLCL / 4SH prepared in Examples 1, 5 and 6 with different addition amounts of pentaerythritol tetrakis-3-mercaptopropionate, as the ratio of -SH to the number of C=C double bonds at the end of A-PLCL increases, the elongation at break and the ultimate tensile stress are both improved, and the elastic modulus is reduced. This means that appropriately increasing the amount of 4SH can further optimize the mechanical properties of the material, making it more elastic and tensile, and further approaching the characteristics of biological soft tissue.
[0117] (III) Inhibition of ROS and vascular smooth muscle cells by Tempol and rapamycin (RAPA)
[0118] Example 7
[0119] According to the method of Example 1, A-3000 / 4SH was prepared as 3D printing ink, and different concentrations of Tempol and RAPA were added and mixed uniformly according to Table 3. The samples were divided into a R0T0 control group without adding any substance, R0T01, R0T05, and R0T1 with only Tempol added, and R1T01, R1T05, and R1T1 with both Tempol and RAPA added.
[0120] Take methacryloyl silk fibroin (SilMa), add PBS to dissolve to 20% (w / v), photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) 0.5% to prepare light-curable SilMa ink, add different concentrations of Tempol according to Table 3, and mix well. A-3000 / 4SH and SilMa inks were successively poured into a 0.8cm pore size silicone circular mold and irradiated with 405nm ultraviolet light for 10 minutes. Finally, a 6mm diameter and 2mm thick circular sample was prepared (A-3000 / 4SH and SilMa were 1mm thick each).
[0121] These treated samples were co-cultured with smooth muscle cells, and the cell proliferation was detected by CCK-8 kit.
[0122] Table 3 Drug composition of the extravascular stent body and SilMa hydrogel layer (wt%)
[0123]
[0124] Fig.14 To verify the synergistic effect of Tempol and rapamycin (RAPA) in inhibiting the growth of vascular smooth muscle cells (VSMCs). Specifically, A-PLCL / 4SH / SilMa samples loaded with different concentrations of Tempol and RAPA were co-cultured with VSMCs and CCK-8 tests were performed for 1, 3, and 5 days. Fig.14 The results showed that the group treated with Tempol alone failed to effectively inhibit the proliferation of smooth muscle cells. This suggests that although Tempol has an antioxidant effect, its use alone has limited effect in inhibiting the proliferation of smooth muscle cells. However, when Tempol was used in combination with RAPA, the proliferation of smooth muscle cells was significantly inhibited. In particular, this inhibitory effect also showed an increasing trend with the increase in Tempol concentration. This suggests that the combined use of Tempol and RAPA not only exerts their respective effects, but also significantly enhances the ability to inhibit the proliferation of smooth muscle cells through a synergistic effect.
[0125] In order to evaluate the ability of Tempol in A-PLCL / 4SH / SilMa to scavenge intracellular reactive oxygen species (ROS), the fluorescent probe DCFH-DA was used to detect reactive oxygen species. Specifically, A-PLCL / 4SH / SilMa samples with different concentrations of Tempol and RAPA were co-cultured with VSMC. On the third day, a reactive oxygen species detection kit was used to induce VMSCs to produce ROS. Confocal laser microscopy was used for observation, and flow cytometry was further used for fluorescence quantitative analysis. The results showed that compared with the positive control group R0T0+ (the component that induced the R0T0 group to produce ROS using the reactive oxygen species detection kit), the release of trace amounts of Tempol in A-PLCL / 4SH could also significantly reduce the level of ROS in VSMCs. As the concentration of Tempol increased, the level of ROS in VSMCs was further reduced to the level of the control group ( Fig.15 a, b, c). The sample loaded with Tempol significantly reduced the level of VSMC ROS under PDGF-BB stimulation, and the addition of RAPA further reduced the level of ROS. This result was confirmed by confocal microscopy and flow cytometry analysis, proving that the combined use of Tempol and RAPA has a more significant inhibitory effect on ROS.
[0126] In order to verify whether RAPA and Tempol have a synergistic effect in inhibiting VSMC proliferation, a VSMC cell co-culture experiment was conducted to test the effects of different treatments on VSMC cells in Table 1. The cell nuclear skeleton was analyzed by confocal microscopy ( Fig.16a, b, c, d, e). In these images, the groups loaded with Tempol and RAPA showed more contractile phenotypes, and the cell aspect ratio of the Tempol and RAPA groups increased significantly compared with the group without RAPA, while the nucleation index, roundness and spreading area of the cells decreased significantly. These observations indicate that the combined application of Tempol and RAPA effectively induced the contractile phenotype conversion of VSMCs and produced significant changes in cell morphology and function, further supporting their synergistic effects in inhibiting intimal hyperplasia and promoting vascular maturation. The results showed that the group treated with Tempol alone failed to effectively inhibit the proliferation of smooth muscle cells. This suggests that although Tempol has an antioxidant effect, its use alone has limited effect in inhibiting the proliferation of smooth muscle cells. However, when Tempol was used in combination with RAPA, the proliferation of smooth muscle cells was significantly inhibited. In particular, this inhibitory effect also showed an increasing trend with the increase in Tempol concentration. This shows that the combined use of Tempol and RAPA not only played their respective roles, but also significantly enhanced the inhibitory ability of smooth muscle cell proliferation through a synergistic effect.
[0127] Finally, we selected the R1T0.5 component for 40-day drug release ( Fig.17 ).pass Fig.17 It can be seen that Tempol in SilMa completed rapid release in the first 3 days (75% release), and Tempol in PLCL / 4SH slowly released in the subsequent time, with a total release of 92% at 40 days. Rapa maintained a slow sustained release, with a release of 48% at 40 days. It was proved that Tempol has rapid burst release (SilMa) and sustained release (A-3000 / 4SH), while rapamycin is sustained release (A-3000 / 4SH), and can be maintained until the arteriovenous fistula is fully mature (6 weeks).
[0128] Example 8 Application Test
[0129] The extravascular stent prepared in Example 2 was implanted in rats, and the process was as follows: Fig.18 The installation process of the arteriovenous fistula extravascular stent is as follows:
[0130] (1) Installation of the stent: The outer layer of the vascular stent is customized according to the size of the blood vessel and installed along the anastomosis between the vein and the artery. Since the stent adopts an open design, it can be inserted into the outer wall of the blood vessel at the fistula from the side and can be operated after the anastomosis, which is conducive to simplifying the operation process and reducing the operation time. The installation of the stent ensures that the blood vessels around the anastomosis are not compressed or deformed by the outside world.
[0131] (2) Hydrogel injection: Use a syringe to inject the hydrogel material into the gap between the stent and the blood vessel wall. The purpose of hydrogel injection is to provide a flexible support medium to act as a buffer between the stent and the blood vessel, while reducing mechanical damage caused by pressure or friction on the blood vessel and guiding blood vessel remodeling. Tempol in the hydrogel can also remove reactive oxygen species at the wound site.
[0132] (3) UV curing: After the hydrogel is injected, a UV light source with a wavelength of 365 to 405 nm is used to irradiate the area for 10 minutes to induce cross-linking and curing of the hydrogel. This process converts the hydrogel into a solid state through photopolymerization, thereby ensuring a stable connection between the stent and the vessel wall.
[0133] After an 8-week observation period, the rats were sacrificed to obtain the vein segment near the anastomosis, and the segment was processed for HE staining. Fig.19 The reconstruction of the vein was shown. After 8 weeks of implantation, the venous tissue showed a good reconstruction effect, and the outer diameter increased significantly, indicating that the stent successfully promoted the expansion and reconstruction of the vein. Further histological analysis showed that new vascular tissue was formed in the venous wall after stent implantation, and no obvious intimal hyperplasia (NIH) was observed. This result shows that the extravascular stent prepared in Example 2 showed excellent effects in promoting venous reconstruction and preventing intimal hyperplasia. These results provide strong support for the effectiveness of the stent in clinical applications and lay the foundation for future research on the design and application of extravascular stents.
Claims
1. An arteriovenous fistula extravascular stent, characterized in that: The extravascular stent is prepared by 3D printing using a bioabsorbable elastomeric resin as printing ink, and includes a tubular arterial stent and a tubular venous stent, wherein the venous stent is anastomosed to the tube wall of the arterial stent at an angle of 30 to 60 degrees to form a "y"-shaped structure; a first notch is provided on the tube wall of the arterial stent, opposite to the anastomosis between the arterial stent and the venous stent, and the first notch extends from one end of the tubular arterial stent to the other end; a second notch is provided on the inner side of the angle between the anastomosis between the venous stent and the arterial stent, extending downward from the two tube openings at the top of the "y"-shaped structure to the anastomosis.
2. The arteriovenous fistula extravascular stent according to claim 1, characterized in that: The bioabsorbable elastomer resin is prepared by the following steps: Step S1: preparing PLCL diol; Step S2: subjecting the terminal hydroxyl groups in the PLCL diol to an acyl chloride, anhydride or glycidyl ester with a carbon-carbon double bond to esterification or transesterification reaction, thereby double-bond-modifying the PLCL diol to obtain A-PLCL; Step S3: A-PLCL is mixed with a cross-linking agent, a free radical inhibitor, and a photoinitiator to obtain a bioabsorbable elastomeric resin that can be used as 3D printing ink.
3. The arteriovenous fistula extravascular stent according to claim 2, characterized in that: The specific method for preparing PLCL diol in step S1 is: adding lactide, ε-caprolactone, diol, and stannous octoate into a reaction kettle, stirring and reacting at 130-160° C. under vacuum and anaerobic conditions for 8-16 hours to obtain poly (L-lactide-co-ε-caprolactone) diol, i.e., PLCL diol.
4. The arteriovenous fistula extravascular stent according to claim 3, characterized in that: The molecular weight of the PLCL diol is 3000-10000, and the viscosity is less than 1000 Pa·s; in step S1, the molar ratio of lactide, ε-caprolactone and diol is 1:1:(0.033-0.088); the diol is selected from one or more of 1,6-hexanediol, ethylene glycol or triethylene glycol.
5. The arteriovenous fistula extravascular stent according to claim 2, characterized in that: In step S2, the acid chloride, acid anhydride and glycidyl ester with a carbon-carbon double bond as the modifier are methacryloyl chloride, methacrylic glycidyl ester and methacrylic anhydride respectively.
6. The arteriovenous fistula extravascular stent according to claim 5, characterized in that: Step S2 specifically comprises dissolving PLCL in dichloromethane, then adding a modifier and triethylamine, and reacting at room temperature for 20 to 24 hours; The molar ratio of the modifier, triethylamine and PLCL diol is 4:4:1; and the concentration of dichloromethane is 15% to 40%.
7. The arteriovenous fistula extravascular stent according to claim 2, characterized in that: In step S3, based on the weight of A-PLCL as a quantitative basis, 1% to 20% of a crosslinking agent, 0.05% to 0.2% of a free radical inhibitor, and 0.2% to 3% of a photoinitiator are added; The crosslinking agent is pentaerythritol tetrakis-3-mercaptopropionate; the free radical inhibitor is 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical or 2,2,6,6-tetramethylpiperidin oxide; and the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide or 2,4,6-trimethylbenzoyl ethyl phosphonate.
8. The arteriovenous fistula extravascular stent according to any one of claims 1 to 7, characterized in that: The inner surface of the extravascular stent body is also coated with hydrogel; the hydrogel is one of methacrylated silk fibroin, methacrylated gelatin, methacrylated hyaluronic acid, methacrylated chitosan, methacrylated sodium alginate, methacrylated chondroitin sulfate or polyethylene glycol acrylate.
9. The arteriovenous fistula extravascular stent according to claim 8, characterized in that: The extravascular stent body and the hydrogel layer are both loaded with drugs. The drugs loaded in the extravascular stent body are selected from one or more of rapamycin, paclitaxel, and 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical; the drug loaded in the gel layer is 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical.
10. The method for preparing an arteriovenous fistula extravascular stent according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Measure the size of the blood vessels based on the patient's ultrasound, CT or MRI results, and use SolidWorks software to build an extravascular stent model that matches the patient's blood vessel size; (2) Mix the drug into the 3D printing ink, import it into the built stent model, set the heating temperature to 50°C, and perform 3D printing; (3) After printing is completed, the stent is placed in anhydrous ethanol for ultrasonic treatment for 10 to 15 minutes, and then cured under a 365 to 405 nm ultraviolet lamp for 10 to 15 minutes to obtain the extravascular stent body.
11. The preparation method according to claim 10, characterized in that: After the arteriovenous fistula is formed, the extravascular stent body is put outside the arteriovenous fistula, and the hydrogel is injected into the gap between the extravascular stent body and the blood vessel using a syringe. A 365-405nm ultraviolet lamp is used to irradiate and cure for 10-12 minutes to obtain a double-layer arteriovenous fistula extravascular stent.